Stimulation of adventitious root formation by laser wounding in rose cuttings: A matter of energy and pattern - Morales-Orellana, Raul Javier; Winkelmann, Traud; Bettin, Andreas; Rath, Thomas (Frontiers in Plant Science, 2022)
Adventitious root (AR) formation is the basis of vegetative propagation in rose, be it via stem cuttings or via stenting. During this process, wounding plays a pivotal role since cell reprogramming takes place at the tissue adjacent to the wound. We investigated the effects of wounding on AR formation on leafy single-node stem cuttings of the rose rootstock R. canina ‘Pfänder’ (codes R02-3 and R02-6) and the cut rose cultivar Rosa ‘Tan09283’ (Registration name ‘Beluga’). Laser wounding treatments were based on the assisted removal of tissue layers located in the bark. The positioning of wounding was studied based on two marking directions: along the cutting base (strip pattern) and around the cutting base (ring pattern). Additionally, the effects of external supply of indole-butyric acid (IBA 1 mg L-1) on rooting were analyzed. Results showed that in order to remove specific tissue layers, the calculation of the laser energy density (J cm-2) in terms of cutting diameter was necessary. Interestingly, the application of energy densities from 2.5 J cm-2 up to approximately 8.5 J cm-2 were sufficient to expose the tissue layers of epidermis up to regions of phloem. Regarding AR formation for R. canina ‘Pfänder’, characterized by a low rooting response, an increase in the rooting percentage was registered when the laser treatment eliminated the tissue up to phloem proximities. Analysis of the nodal position showed that bud location was a preferential place for AR formation independently of wounding treatment. In case of Rosa ‘Tan09283’, laser treatments did not reduce its high rooting capacity, but an apparent reduction in rooting quality due to an investment in tissue healing was observed when wounding reached deeper layers such as parenchyma and sclerenchyma. Results also showed a strong AR formation directly from wounded regions in case of Rosa ‘Tan09283’ specifically when the wound was located below the axillary bud. In conclusion, wounding by assisted-elimination of layers by laser can induce positive effects on AR formation of single-node stem cuttings of the rose if energy applied is able to expose phloem proximities, a longitudinal orientation, and relative position to the axillary bud are considered.